Oxidative stress markers: can they be used to evaluate human sperm quality? - Cruz, Daniel Filipe (2020)
Objective To study the effects of an acute lifestyle change in human semen oxidative stress (OS) by applying seminal parameters and OS markers and to study the feasibility of mid-infrared spectroscopy with Fourier transform infrared spectroscopy (FT-IR) as a complementary tool to evaluate the effects of OS on human sperm samples. Material and methods Sperm samples were collected from healthy male students (n=8) who voluntarily submitted themselves to acute lifestyle changes during academic festivities. The samples were obtained before and after the academic festivities and were compared by basic semen analyses and OS markers, namely with thiobarbituric acid reactive species (TBARS) and total thiol (SH) groups by spectrophotometric assays and carbonyl (CO) groups by slot blot. The samples were also submitted for spectroscopic analysis to evaluate the feasibility of FT-IR coupled with multivariate analysis to calibrate OS biomarkers. Statistical analysis was performed applying paired Wilcoxon tests. Results Acute lifestyle alterations during academic week festivities were associated with a significant decrease in the percentage of normal spermatozoa in the ejaculate (p=0.011) and a decrease in sperm concentration and in semen volume. Regarding OS, acute lifestyle changes promoted a significant increment of TBARS (p=0.018) and an increasing trend in the SH group. With FT-IR and multivariate analysis, it was possible to develop calibration models to the following protein OS biomarkers: SH groups and CO. Conclusions Acute lifestyle changes during academic festivities have negative effects on sperm quality, in both conventional seminal parameters and OS markers. The evaluation of OS biomarkers and FT-IR could improve andrology diagnosis and therapeutic follow-up.